TPU (thermoplastic polyurethane) sole surface treating agent and preparation method thereof

By using treatment agents with polarization component A, antioxidant component B, anti-hydrolysis component C, and anti-bacterial and mildew resistance on the surface of the TPU sole, the problems of TPU sole single color and not hydrolysis resistance are solved, and its significant improvement in oxidation resistance, hydrolysis resistance, hydrophobicity and anti-bacterial and mildew resistance are achieved, extending the service life and widening the application scenarios.

CN119639344APending Publication Date: 2025-03-18JINJIANG XINFENG CHEM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411877352.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In actual applications, TPU soles have problems such as single color, easy to fall off when applied to the color, not resistant to hydrolysis, easy to produce macula, difficult to clean up dust deposits, falling or cracking of TPU particles, poor antibacterial performance, and easy to appear mold spots.

Method used

Using a TPU sole surface treatment agent, the treatment agent is prepared by optimizing the material ratio and addition order of the compound modified aqueous polyurethane by carbon nanotubes, silver nitrate, sodium alginate and camellia oil, etc.

Benefits of technology

The TPU sole treated with this treatment agent has excellent coloring, oxidation resistance, hydrolysis resistance, hydrophobicity and antibacterial and mildew resistance, extending service life and widening application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a TPU (thermoplastic polyurethane) sole surface treating agent. The TPU sole surface treating agent comprises 30-50 parts of a component A, 5-10 parts of a component B, 8-12 parts of a component C, 3-8 parts of a component D and 10-20 parts of a solvent, the component A comprises 20-40 parts of hydrogenated castor oil, 3-5 parts of nano titanium dioxide, 2-4 parts of glass beads, 0.5-1.5 parts of sericite, 1-2 parts of a coupling agent and 2-5 parts of an isocyanate bridging agent; the components are prepared from the following components in parts by weight: 5 to 10 parts of vinyl trimethoxy silane, 2 to 5 parts of polycarbodiimide, 1 to 3 parts of 4-tert-butylcatechol and 1 to 4 parts of azodiformate; the component C is prepared from 1 to 3 parts of carbon nanotubes, 2 to 5 parts of silver nitrate, 0.5 to 1.5 parts of sodium alginate and 10 to 30 parts of ethanol; the component D is camellia oil composite modified waterborne polyurethane; the solvent is low-molecular-weight organic dicarboxylic acid. The TPU sole is subjected to surface treatment by the surface treating agent, so that the coloring performance, oxidation resistance, hydrolysis resistance, hydrophobicity, antibacterial and mildew-proof performance and the like of the TPU sole are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of surface treatment agent preparation, and specifically relates to a TPU sole surface treatment agent and a preparation method thereof. Background Art

[0002] Thermoplastic polyurethane elastomer (TPU) has a special soft and hard segment block copolymer structure and is a high-performance elastic material with excellent physical and mechanical properties, such as high wear resistance, flexibility, oil resistance and chemical resistance. TPU is widely used in the fields of automobiles, electronics, medical treatment, footwear, sports equipment, etc.

[0003] Patent CN109853253B proposes a TPU flying woven upper, which is made by weaving a semi-finished flying woven upper with TPU yarn, then impregnating it with an antibacterial agent, and coating the surface of the upper with a polyurethane coating to obtain the TPU flying woven upper; TPU yarn has the characteristics of high elasticity and smoothness, and the upper woven with TPU has the basic condition of being free of ironing, and then it is impregnated with an antibacterial agent to make it antibacterial, and coated with a polyurethane coating to make it breathable and waterproof, and the obtained upper has great market advantages.

[0004] Patent CN102396838B proposes a functional shoe head and tail TPU shock-absorbing sole, including an EVA upper layer, a TPU middle layer and a rubber bottom layer. The characteristic is that the stress-bearing parts of the TPU middle layer corresponding to the forefoot and the rear foot are convex toward the EVA upper layer and are arc-shaped along the length of the sole. Under the convex part is a hollow shock-absorbing cavity that can buffer the pressure when the foot is subjected to force at any angle in contact with the ground, thereby achieving a shock-absorbing effect to meet the needs of various different sports.

[0005] The application of TPU materials in footwear exhibits properties such as high elasticity, high shock absorption and soft feel, but in actual applications, there are also problems such as single color and easy coloring to fall off; it is not resistant to hydrolysis and will produce yellow spots over time; dust is easily deposited and difficult to clean; it will cause TPU particles to fall off and even crack; the antibacterial performance is poor and there will be mildew spots and other problems. Summary of the invention

[0006] The purpose of the present invention is to provide a TPU sole surface treatment agent and a preparation method thereof. Through the combined action of a polarization component A, an antioxidant component B, an anti-hydrolysis component C, and an antibacterial and mildew-proof component D, the TPU sole treated with the treatment agent has excellent colorability, oxidation resistance, hydrolysis resistance, hydrophobicity, antibacterial and mildew-proof effects, thereby broadening the application scenarios of the TPU sole.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: A TPU sole surface treatment agent comprises, by weight, 30-50 parts of component A, 5-10 parts of component B, 8-12 parts of component C, 3-8 parts of component D and 10-20 parts of solvent.

[0008] Preferably, the component A comprises, by weight, 20-40 parts of hydrogenated castor oil, 3-5 parts of nano titanium dioxide, 2-4 parts of glass microspheres, 0.5-1.5 parts of sericite, 1-2 parts of coupling agent and 2-5 parts of isocyanate bridging agent.

[0009] Preferably, the component B comprises, by weight, 5-10 parts of vinyltrimethoxysilane, 2-5 parts of polycarbodiimide, 1-3 parts of 4-tert-butylcatechol and 1-4 parts of azodicarboxylic acid ester.

[0010] Preferably, the component C comprises, by weight, 1-3 parts of carbon nanotubes, 2-5 parts of silver nitrate, 0.5-1.5 parts of sodium alginate and 10-30 parts of ethanol.

[0011] Preferably, the component D is a camellia oil-composite modified waterborne polyurethane; and the solvent is a low molecular weight organic dicarboxylic acid.

[0012] The preparation method of the above-mentioned TPU sole surface treatment agent comprises the following steps: S1: prepare component A and component B respectively; S2: prepare component C and component D respectively; S3: 30-50 parts of component A, 5-10 parts of component B, 8-12 parts of component C, 3-8 parts of component D and 10-20 parts of solvent are mixed, ultrasonically treated, and allowed to stand to obtain the TPU sole surface treatment agent.

[0013] Preferably, the preparation process of component A in step S1 is: mix 20-40 parts of hydrogenated castor oil, 1-2 parts of coupling agent and 2-5 parts of isocyanate bridging agent, wherein the castor oil has a hydroxyl value of 160-180 mg / KOH; stir at a temperature of 100-120°C for 15-20 minutes, then add 3-5 parts of nano titanium dioxide and stir for 3-5 minutes, then add 2-4 parts of glass beads and stir for 3-5 minutes, then add 0.5-1.5 parts of sericite and stir for 40-60 minutes to obtain component A.

[0014] Preferably, the preparation process of component B in step S1 is: take 5-10 parts of vinyltrimethoxysilane, 2-5 parts of polycarbodiimide, 1-3 parts of 4-tert-butylcatechol and 1-4 parts of azodicarboxylate, stir and mix at a temperature of 120-130° C. for 1-3 hours to obtain component B.

[0015] Preferably, the preparation process of component C in step S1 is as follows: 1-3 parts of carbon nanotubes and 10-30 parts of ethanol are stirred at a temperature of 80-100°C for 15-25 minutes, and then 2-5 parts by mass of 80% silver nitrate aqueous solution and 1-3 parts by mass of 85% barium sulfate aqueous solution are added while stirring, and the magnetic field strength is 2.1-2.6T, 75-85KW for 1-3 hours; then 0.5-1.5 parts of sodium alginate are added, and the mixture is rapidly stirred for 25-45 minutes to obtain component C. Preferably, the preparation process of component D in step S1 is: mix 15-25 parts of camellia oil, 0.5-1.5 parts of N,N-dimethylformamide, 01-0.3 parts of dibutyltin dilaurate, 10-20 parts of polyether and 5-10 parts of isophorone diisocyanate, and stir and mix at a temperature of 110-130° C. for 35-45 minutes to obtain component D.

[0016] Compared with the prior art, the advantages and beneficial effects of the present invention are: In the preparation of TPU surface treatment agent, the present invention uses hydrogenated castor oil, coupling agent, isocyanate bridging agent, nano titanium dioxide, glass microbeads, and sericite as main components, and optimizes the material ratio and the order of addition to polarize the surface, so that it is easy to color according to different customer needs and design requirements in the later stage; uses vinyl trimethoxysilane, polycarbodiimide, 4-tert-butylcatechol, and azodicarboxylate as main components to improve the water resistance and hydrophobicity of the treatment agent and extend its service life; uses carbon nanotubes, silver nitrate, and sodium alginate to improve the antibacterial and mildew-proof properties of the treatment agent, and has good dispersibility and uniform performance; uses camellia oil composite modified waterborne polyurethane to improve its weather resistance and prevent yellowing caused by long-term ultraviolet irradiation. The TPU sole treated with the surface treatment agent of the present invention has a wider application and a longer service life. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] The raw materials used in the present invention are as follows: Hydrogenated castor oil was purchased from Shanghai Yuanye Biotechnology Co., Ltd. S29765; titanate coupling agent was purchased from Shanghai Dongjindu New Material Technology Co., Ltd. 14; isocyanate bridging agent was purchased from Guangzhou Zhongtuli New Material Technology Co., Ltd. BT-70F; nano titanium dioxide was purchased from Shanghai Jiader Chemical Technology Co., Ltd. 125; glass microspheres were purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd. 05131; sericite was purchased from Nantong Runfeng Petrochemical Co., Ltd. 1324; vinyl trimethoxysilane was purchased from Hubei Chenghai Chemical Co., Ltd. CH0020; polycarbodiimide was purchased from Foshan Ruisheng Plastic Co., Ltd. 051; carbon nanotubes were purchased from Shanghai Yuanye Biotechnology Co., Ltd. T19281; camellia oil was purchased from Jishui County Juyuantang Natural Flavor Oil Co., Ltd. 135; N,N-dimethylformamide was purchased from Jinan Feiyue Chemical Co., Ltd. 58; dibutyltin dilaurate was purchased from Nanjing Dulai Biotechnology Co., Ltd. 971; polyether was purchased from Wuhan Dingxintong Pharmaceutical Co., Ltd. 984; isophorone diisocyanate was purchased from Wuhan Kanos Technology Co., Ltd. 3011.

[0019] Example 1 This embodiment provides a method for preparing a TPU sole surface treatment agent, comprising the following steps: S1: Mix 20g hydrogenated castor oil (hydroxyl value is 160mg / KOH), 1g titanate coupling agent HY-311 and 2g isocyanate bridging agent; stir at 100℃ at a speed of 500r / min for 15min, then add 3g nano titanium dioxide at a speed of 550r / min for 3min, then add 2g glass micro beads at a speed of 600r / min for 3min, then add 0.5g sericite, and stir at a speed of 800r / min for 40min to obtain component A; Take 5g of vinyltrimethoxysilane, 2g of polycarbodiimide, 1g of 4-tert-butylcatechol and 1g of azodicarboxylate, stir and mix at a temperature of 120°C and a speed of 800r / min for 1h to obtain component B; S2: Take 1g of carbon nanotubes and 10g of ethanol and stir at 400r / min for 15min at 80℃, then add 2g of 80% silver nitrate aqueous solution and 1g of 85% barium sulfate aqueous solution while stirring at 450r / min, and react for 1h at a magnetic field intensity of 2.1T and 65KW; then add 0.5g of sodium alginate and stir at 800r / min for 25min to obtain component C; 15 g of camellia oil, 0.5 g of N,N-dimethylformamide, 0.1 g of dibutyltin dilaurate, 10 g of polyether and 5 g of isophorone diisocyanate were mixed, and stirred at a temperature of 110° C. and a speed of 600 r / min for 35 min to obtain component D; S3: 30 g of component A, 5 g of component B, 8 g of component C, 3 g of component D and 10 g of adipic acid were mixed for 20 min, and then ultrasonically treated at a power of 1000 W for 10 min to obtain the TPU sole surface treatment agent.

[0020] Example 2 This embodiment provides a method for preparing a TPU sole surface treatment agent, comprising the following steps: S1: Mix 40g hydrogenated castor oil (hydroxyl value is 180mg / KOH), 2g titanate coupling agent HY-311 and 5g isocyanate bridging agent; stir at 120°C at a rate of 500r / min for 20min, then add 5g nano titanium dioxide at a rate of 550r / min for 5min, then add 4g glass microspheres at a rate of 600r / min for 5min, then add 1.5g sericite, and stir at a rate of 800r / min for 60min to obtain component A; Take 10g of vinyltrimethoxysilane, 5g of polycarbodiimide, 3g of 4-tert-butylcatechol and 4g of azodicarboxylate, stir and mix at a temperature of 130°C and a speed of 800r / min for 3h to obtain component B; S2: 3g of carbon nanotubes and 30g of ethanol were stirred at 500r / min for 25min at 100℃, and then 5g of 80% silver nitrate aqueous solution and 3g of 85% barium sulfate aqueous solution were added while stirring at 450r / min, and the magnetic field was kept at 2.6T, 85KW for 3h; then 1.5g of sodium alginate was added and stirred at 800r / min for 45min to obtain component C; 25 g of camellia oil, 1.5 g of N,N-dimethylformamide, 0.3 g of dibutyltin dilaurate, 20 g of polyether and 10 g of isophorone diisocyanate were mixed, and stirred at a temperature of 130° C. and a speed of 600 r / min for 45 min to obtain component D; S3: 50 g of component A, 10 g of component B, 12 g of component C, 8 g of component D and 20 g of adipic acid were mixed for 40 min, and then ultrasonically treated at a power of 1200 W for 15 min to obtain the TPU sole surface treatment agent.

[0021] Example 3 This embodiment provides a method for preparing a TPU sole surface treatment agent, comprising the following steps: S1: 35g hydrogenated castor oil (hydroxyl value is 170mg / KOH), 1.5g titanate coupling agent HY-311 and 3g isocyanate bridging agent were mixed; stirred at 110°C at a rate of 500r / min for 18min, then 4g nano titanium dioxide was added at a rate of 550r / min and stirred for 4min, then 3g glass micro beads were added at a rate of 600r / min and stirred for 4min, then 1g sericite was added and stirred at a rate of 800r / min for 50min to obtain component A; 7 g of vinyl trimethoxysilane, 4 g of polycarbodiimide, 2 g of 4-tert-butylcatechol and 3 g of azodicarboxylate were mixed at a temperature of 125° C. and a speed of 800 r / min for 2.5 h to obtain component B; S2: 2g of carbon nanotubes and 25g of ethanol were stirred at 95°C at a rate of 500r / min for 20min, and then 4g of 80% silver nitrate aqueous solution and 2g of 85% barium sulfate aqueous solution were added while stirring at a rate of 450r / min, and the magnetic field was set at 2.4T, 80KW for 2h; then 1g of sodium alginate was added and stirred at a rate of 800r / min for 35min to obtain component C; 22 g of camellia oil, 1 g of N,N-dimethylformamide, 0.2 g of dibutyltin dilaurate, 15 g of polyether and 8 g of isophorone diisocyanate were mixed, and stirred at a temperature of 120° C. and a speed of 500 r / min for 40 min to obtain component D; S3: 45 g of component A, 7 g of component B, 10 g of component C, 5 g of component D and 15 g of adipic acid were mixed for 35 min, and then ultrasonically treated for 12 min at a power of 1100 W to obtain the TPU sole surface treatment agent.

[0022] Comparative Example 1 The difference between this comparative example and Example 1 is that the titanate coupling agent HY-311 and the isocyanate bridging agent are missing in step S1, and the other steps are the same.

[0023] Comparative Example 2 The difference between this comparative example and Example 1 is that vinyltrimethoxysilane is missing in step S1, and the other steps are the same.

[0024] Comparative Example 3 The difference between this comparative example and Example 1 is that carbon nanotubes are missing in step S2, and the other steps are the same.

[0025] Comparative Example 4 The difference between this comparative example and Example 1 is that sodium alginate is missing in step S2, and the other steps are the same.

[0026] Comparative Example 5 The difference between this comparative example and Example 1 is that component D is missing in step S3, and the other steps are the same.

[0027] Performance Test: Hydrolysis resistance test: Place the sole in a wet heat test box with a humidity of 95% RH and a temperature of 70°C for 168 hours, and observe the changes in the sole; UV resistance test: Irradiate the sole under a UV light with an energy of 440W and a wavelength of 365nm for 8 hours, and observe the changes in the sole; Friction test: Use a test instrument to hang 280-mesh sandpaper, and rub the sole surface back and forth 50 times with a force of 500kg to observe the changes in the sole surface; Coloring performance: Use a treatment agent to brush the TPU sole that needs to be colored to remove the grease and adsorbed dust on the sample surface, and use a flexible brush to evenly brush the solution composed of yellow pigment / EVA resin / ethyl acetate (concentration of 10000ppm) on the surface of the sample that needs to be colored, and dry it at low temperature to make a TPU sole with uniform distribution of pigments, and then use a friction test to test its performance; Use the oscillation method to test the performance of antibacterial agents. The results are shown in the table below.

[0028] Table 1

[0029] It can be seen from the above performance test results that Examples 1-3 have excellent performance in terms of anti-oxidation, hydrolysis resistance, antibacterial, etc. In particular, the comprehensive performance of Example 3 is the most outstanding. However, since Comparative Examples 1-5 do not adopt the necessary technical solutions, their corresponding performance tests are significantly worse than those of the Examples. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.

[0030] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A TPU sole surface treatment agent, characterized in that: Calculated by weight, it includes 30-50 parts of component A, 5-10 parts of component B, 8-12 parts of component C, 3-8 parts of component D and 10-20 parts of solvent.

2. A TPU sole surface treatment agent according to claim 1, characterized in that: The component A comprises, by weight, 20-40 parts of hydrogenated castor oil, 3-5 parts of nano titanium dioxide, 2-4 parts of glass microspheres, 0.5-1.5 parts of sericite, 1-2 parts of coupling agent and 2-5 parts of isocyanate bridging agent.

3. A TPU sole surface treatment agent according to claim 1, characterized in that: The component B comprises, by weight, 5-10 parts of vinyltrimethoxysilane, 2-5 parts of polycarbodiimide, 1-3 parts of 4-tert-butylcatechol and 1-4 parts of azodicarboxylic acid ester.

4. A TPU sole surface treatment agent according to claim 1, characterized in that: The component C comprises, by weight, 1-3 parts of carbon nanotubes, 2-5 parts of silver nitrate, 0.5-1.5 parts of sodium alginate and 10-30 parts of ethanol.

5. A TPU sole surface treatment agent according to claim 1, characterized in that: The component D is a camellia oil-composite modified waterborne polyurethane; and the solvent is a low molecular weight organic dicarboxylic acid.

6. A method for preparing a TPU sole surface treatment agent, characterized in that: The steps include: S1: prepare component A and component B respectively; S2: prepare component C and component D respectively; S3: 30-50 parts of component A, 5-10 parts of component B, 8-12 parts of component C, 3-8 parts of component D and 10-20 parts of solvent are mixed, ultrasonically treated, and allowed to stand to obtain the TPU sole surface treatment agent.

7. The method for preparing a TPU sole surface treatment agent according to claim 6, characterized in that: The preparation process of component A in step S1 is as follows: 20-40 parts of hydrogenated castor oil, 1-2 parts of coupling agent and 2-5 parts of isocyanate bridging agent are mixed, and the hydroxyl value of the castor oil is 160-180 mg / KOH; stirring at a temperature of 100-120° C. for 15-20 min, then adding 3-5 parts of nano titanium dioxide and stirring for 3-5 min, then adding 2-4 parts of glass beads and stirring for 3-5 min, then adding 0.5-1.5 parts of sericite and stirring for 40-60 min to obtain component A.

8. The method for preparing a TPU sole surface treatment agent according to claim 6, characterized in that: The preparation process of component B in step S1 is as follows: take 5-10 parts of vinyltrimethoxysilane, 2-5 parts of polycarbodiimide, 1-3 parts of 4-tert-butylcatechol and 1-4 parts of azodicarboxylate, stir and mix at a temperature of 120-130° C. for 1-3 hours to obtain component B.

9. The method for preparing a TPU sole surface treatment agent according to claim 6, characterized in that: The preparation process of component C in step S1 is as follows: 1-3 parts of carbon nanotubes and 10-30 parts of ethanol are stirred at a temperature of 80-100°C for 15-25 minutes, and then 2-5 parts by mass of 80% silver nitrate aqueous solution and 1-3 parts by mass of 85% barium sulfate aqueous solution are added while stirring, and the magnetic field strength is 2.1-2.6T, 75-85KW for 1-3 hours; then 0.5-1.5 parts of sodium alginate are added, and the mixture is rapidly stirred for 25-45 minutes to obtain component C.

10. The method for preparing a TPU sole surface treatment agent according to claim 6, characterized in that: The preparation process of component D in step S1 is as follows: 15-25 parts of camellia oil, 0.5-1.5 parts of N,N-dimethylformamide, 01-0.3 parts of dibutyltin dilaurate, 10-20 parts of polyether and 5-10 parts of isophorone diisocyanate are mixed, and stirred at a temperature of 110-130° C. for 35-45 minutes to obtain component D.

Citation Information

Patent Citations

  • TPU damping soles for heads and tail parts of functional shoes

    CN102396838B

  • A TPU flyknit upper

    CN109853253B

  • Enhanced optical lens material

    CN109054358A

  • Nano-silver modified polymer coating material and preparation method thereof

    CN114133859A

  • TPU (thermoplastic polyurethane) outsole shell treating agent and preparation method thereof

    CN116987432A